Determinan Indeks Pembangunan Manusia Jawa Timur Tahun 2020 dengan Pendekatan Geograpichally Weighted Regression - Khaerul Agus; Joko Ade Nursiyono; Chusnul Chotimah (Journal of Regional Economics Indonesia, 2022)
HDI is an outcome indicator that measures how much of a development impact is felt by the community. In addition to being a measure of development success, HDI is also used as an important component of Key Performance Indicators (IKU), especially contained in targets 7 and 9. Data mentions that HDI increases every year, especially the East Java region. However, the speed of HDI has not been accompanied by a decreased maternal and infant mortality rate. The study aimed to look at the spatial influence of the percentage of maternal and infant mortality on HDI. The study also included dependency ratio variables and gender empowerment indices to sharpen the analysis. The approaches used are OLS regression and Geographically Weighted Regression (GWR). By looking at the lowest AIC value and the highest R Square, the best GWR model is obtained. A SQUARE GWR value of 0.7226 indicates the model's ability to explain the proportion of HDI diversity is 72.26 percent, while the rest is determined by other variables outside the model.